Trauma biomechanics : an introduction to injury biomechanics /: an introduction to injury biomechanics. (2019) - Schmitt, Kai-Uwe; Niederer, P (Peter); Cronin, Duane S; Morrison, Barclay; Muser, Markus H; Walz, Felix H
No abstract available